Determinación del costo de producción de cinco platos ofertados en el bar estudiantil del colegio nacional Mejía de la Ciudad de Quito, periodo: noviembre 2014 - Terán Noriega, Myrian Cecilia (2016)
This document is based on the application of the knowledge acquired at the National University of Loja, making a collection of documents and data to thereby formalizing records the information gathered in the Student Bar of Mejia College of Quito, in which they proposed the "DETERMINATION OF PRODUCTION COST OF FIVE DISHES OFFERED IN BAR NATIONAL COLLEGE STUDENT MEJÍA QUITO CITY, PERIOD: NOVEMBER 2014" Additionally, this work as a pre-requisite to obtain the Engineering degree in Accounting and Auditing once having completed university studies and comply Rule 129 Academic Board of the National System of Higher Education in the setting is performed as graduation requirement for the development of a research paper (thesis). This document was given to compliance objectives, starting with an initial inventory, develop a chart of accounts according to the requirements of the company, making the necessary records relevant to determining the cost of production and the development with the recommendations and conclusions.